2018
DOI: 10.13189/ujer.2018.061109
|View full text |Cite
|
Sign up to set email alerts
|

The Readiness Level of Teachers in Science, Technology, Engineering and Mathematics Education

Abstract: The aim of this research is to determine the viewpoints and readiness of class, mathematics and science teachers on STEM (Science, Technology, Engineering and Mathematics) Education. The other aims are to determine different between branches and seniority in the readiness of teachers on STEM Education. The review method was used in the study the sampling of the study consisted of 371 teachers, who were selected randomly from Siirt and Batman. A questionnaire was developed by the authors of the study to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…Their interest in STEM education shows their eagerness to learn and improve their teaching skills to integrate STEM education, especially in designing and implementing issues. This interest was also found in former research that concluded that teachers need comprehensive training in STEM education (Asiroglu & Akran, 2018;Osadchyi, Valko & Kushnir, 2019). This notion is also related to the essence of teachers' role as a central factor in nurturing students' talent development and holding views and experiences that will influence their STEM instruction.…”
Section: Possibility and Experiences Of Stem Education Implemented In...mentioning
confidence: 56%
See 1 more Smart Citation
“…Their interest in STEM education shows their eagerness to learn and improve their teaching skills to integrate STEM education, especially in designing and implementing issues. This interest was also found in former research that concluded that teachers need comprehensive training in STEM education (Asiroglu & Akran, 2018;Osadchyi, Valko & Kushnir, 2019). This notion is also related to the essence of teachers' role as a central factor in nurturing students' talent development and holding views and experiences that will influence their STEM instruction.…”
Section: Possibility and Experiences Of Stem Education Implemented In...mentioning
confidence: 56%
“…Exploration of teacher readiness in specific STEM professional development programs concluded that collaboration among teachers is essential (Rukoyah, Widodo & Rochintaniawati, 2020). On the other hand, identification of teacher readiness based on their understanding of each component of STEM with difficulties in engineering component was also found (Asiroglu & Akran, 2018). Science teachers tend to feel confident with their ability in teaching the science subject, therefore we argue that their readiness depends on each specific subject that they taught and exploration of teacher readiness in a specific science subject such as physics is needed.…”
Section: Defining Teacher Readiness In Stem Educationmentioning
confidence: 99%
“…The education project contributed positively to the development of pedagogical competences such as enriching the lesson plan in terms of affective and cognitive dimensions, preparing an assessment tool suitable for the subject and student level, and ensuring objective-subjectmeasurement tool harmony. Pre-service teachers who have problems while preparing a lesson plan will also have problems interacting with the students during the implementation of the plan (Aşiroğlu & Koç Akran, 2018). Therefore, the pre-service teachers should experience the proficiency in terms of preparing lesson plans by being aware of the holistic needs of students before starting teaching.…”
Section: Discussionmentioning
confidence: 99%
“…yang sangat penting untuk pendidikan dan pengembangan karena lulusan sekolah memerlukan keterampilan, seperti kreativitas, imajinasi, dan inovasi untuk mengatasi setiap tantangan produksi dan pengembangan yang muncul dalam kehidupan mereka termasuk dunia kerja (Mitana, 2018). Kemampuan guru masih dalam taraf cukup profesional dalam kegiatan yang melibatkan analisis berdasarkan Taksonomi Bloom, dan dalam kegiatan yang meningkatkan keterampilan di tingkat tinggi sehingga perlu menekankan peningkatan guru dalam meningkatkan kemampuan berpikir siswa dengan memberikan sebuah permasalahan (Soal ujian) yang Higher Order Thinking Skill Berbasis Pemecahan Masalah untuk Meningkatkan Hasil Belajar Berorientasi Pembentukan Karakter Siswa (Asiroglu & Akran, 2018). Meningkatkan kemampuan berpikir siswa dengan jenis soal yang dibuat oleh guru masih dalam tingkat rendah (Köksal & Ulum, 2018).…”
Section: Pembahasan Demografi Personality Profesionalitas Guru Tingkat Berpikir Siswa Dan Jenis Soal Ujianunclassified